Management, risk factors and associated causes of road traffic accidents in Erbil city, Kurdistan- Iraq - Kamal Yasen, Muhsen (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objective: Traffic accidents are a contributing factor to any loss of life, property, or services. It occurs when a vehicle collides with another vehicle or object. Certain elements will manifest, resulting in harm and potentially preventable incidents, and reduced by using the right strategies. These losses came from lower production and recovery costs. This study aimed to identify management, risk factors, and associated causes of traffic accidents in Erbil city. Methods: This retrospective study was conducted from January 2008 to December 2023, in Erbil City, Iraq. Data was collected form national Incident monitoring system (NIMS) at directorate of Health, Erbil, KRG, Iraq. All acquired data were compiled until August 2020; thereafter, certain cases were excluded and not gathered due to the COVID-19 lockdown. Results: A total of 41669 road traffic accidents were recorded during 2008-2023. A high incidence was found in 2023, and 2022 accounted for 4769 (11.44%), and 4613 (11.07%). While low prevalence was seen in 2012 (7.96%), 2015 (7.47%), 2016 (7.40%), 2014 (7.35%), 2013 (7.21%), 2018 (7.19%), 2017 (6.89%), 2021(5.96%), 2019 (5.04%), 2020 (4.66%), 2011 (3.10%), 2010 (3%), 2008 (2.45%), and 2009 (1.71%). Among all accidents with a high prevalence were car crashes (79.66%), followed by a lower prevalence of motorcycles (10.74%), pedestrians (7.53%), bicycles (1.91%), and car explosion (0.13%). Conclusion: Human conduct is linked to a high rate of traffic accidents leading to injuries and fatalities. Road accidents have become a significant public health hazard. A new strategy for mitigating the seriousness of this issue is necessary.